Gymnasts, distance runners, anorexics body composition and menstrual status - Bale, P.; Doust, J.; Dawson, D. (The Journal of Sports Medicine and Physical Fitness, 1996)
Ten top class female distance runners, ten female anorexics and twenty female gymnasts of a similar age were compared for height, mass, %fat, fat mass, lean body mass, age of menarche and incidence of amenorrhoea. The mean age of the distance runners, anorexics, and gymnasts was 13.6 years, 14.7 years, and 13.3 years respectively. In comparison to normal data on females of a similar age they were shorter, lighter, had lower fat masses, and %fat, and the gymnasts and anorexics had lower lean body masses. However, the gymnasts and runners had higher lean body masses compared with the anorexic group. There were no significant differences in body composition by hydrostatic weighing but of these three groups the anorexics tended to have the highest total skinfold, %fat and fat masses. Only 20% of the gymnasts, 40% of the runners and 70% of the anorexics had started menstruating compared with 95% of girls of a similar age. Of the girls in our study who had started menstruating one gymnast, (25% of sub-group) two runners (50% of sub-group) and seven anorexics (100% of sub-group) had developed secondary amenorrhoea. The low body masses, low fat masses, delayed menarche and secondary amenorrhoea in athletes are discussed in relation to low caloric intake, stress, hormone levels, high training loads and genetic factors. Our data demonstrating no significant differences in body composition variables between the three groups of young girls, support the main contention that this type of physique may arise through different mechanisms leading to a common outcome, but without a proven causal link between anorexia and athletic performance.